2018
DOI: 10.1039/c8mh00223a
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism controls the degree of charge transfer in a molecularly doped semiconducting polymer

Abstract: Jacobs et al. present the first observation of both fractional and integer charge transfer phases in a single OSC:dopant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
216
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(235 citation statements)
references
References 44 publications
19
216
0
Order By: Relevance
“…The dopant concentration dependent behavior observed here is similar to that for doping of P3HT with F 4 TCNQ, where maximal conductivities of 1-3 S cm −1 were achieved at dopant concentrations of around 10-25%. [4,32,60] The decrease in conductivity at higher dopant concentration is typically due to a loss in film crystallinity as well as increased Coulomb scattering upon excessive incorporation of dopants. This decreases the charge carrier mobility and thus the conductivity.…”
Section: Indications For Bipolarons From Optical Absorption and Condumentioning
confidence: 99%
See 1 more Smart Citation
“…The dopant concentration dependent behavior observed here is similar to that for doping of P3HT with F 4 TCNQ, where maximal conductivities of 1-3 S cm −1 were achieved at dopant concentrations of around 10-25%. [4,32,60] The decrease in conductivity at higher dopant concentration is typically due to a loss in film crystallinity as well as increased Coulomb scattering upon excessive incorporation of dopants. This decreases the charge carrier mobility and thus the conductivity.…”
Section: Indications For Bipolarons From Optical Absorption and Condumentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Today, it is commonly accepted that molecular doping of polymers, in general, leads to the formation of polarons as charge carriers, predominantly. [1,2,24,25] Positive bipolaron formation in P3HT has been evidenced only upon electrochemical doping and doping with FeCl 3 (a small inorganic Lewis acid dopant), [26][27][28][29] but not with the molecular dopants employed nowadays, such as 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F 4 TCNQ), [4,[30][31][32] 1,3,4,5,7,8hexafluoro-11,11,12,12-tetracyanonaphtho-2,6-quinodimethane (F 6 TCNNQ), [33] hexacyano-trimethylene-cyclopropane (CN6-CP), [34] and molybdenum tris[1,2-bis(trifluoromethyl)ethane-1,2-dithiolene] (Mo(tfd) 3 ). [35,36] While bipolaron formation was considered to occur in some of these studies, [22,37] no compelling evidence was provided, particularly as no clear differentiation of polaron and bipolaron abundance in dependence of dopant concentration was possible.…”
Section: Introductionmentioning
confidence: 99%
“…13 Consequently, implications of the presence of aggregates in solution of P3HT mixed with a dopant in solution were also investigated. [14][15][16][17] The abundance of re-P3HT aggregates in solution was reported to increase upon addition of molecular p-type dopants, with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F 4 TCNQ) being the one most frequently used, and was ascribed to decreased solubility of the corresponding ionized species after ion pair (IPA) formation (doping involving integer electron transfer). 18,19 It was shown that aggregation occurs more readily for solution-mixed doping as compared to sequential doping of re-P3HT thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Moulé and coworkers also found a greater change in conductivity with ionized dopant concentration for sequentially processed films, where the P3HT films retained the lattice parameters of the neutral films . The exact degree to which the dopants penetrate the aggregates, and the aggregate crystal structure will depend on the solvent, temperature, and when the dopant is added . While we cannot determine the exact degree of dopant penetration into the aggregates, our results suggest that there is more penetration into the aggregates when the aggregates form in the presence of dopant rather than when the dopant is added after their formation.…”
mentioning
confidence: 52%